Combined impact of ADHD and insomnia symptoms on quality of life, productivity, and health care use in the general population. Issue 1 (29th January 2022) - van Andel, Emma; ten Have, Margreet; Bijlenga, Denise; Beekman, Aartjan T. F.; de Graaf, Ron; Sandra Kooij, J. J.
Abstract: Background: Both attention-deficit/hyperactivity disorder (ADHD) and insomnia have been independently related to poorer quality of life (QoL), productivity loss, and increased health care use, although most previous studies did not take the many possible comorbidities into account. Moreover, ADHD and insomnia often co-occur. Symptoms of ADHD and insomnia together may have even stronger negative effects than they do separately. We investigated the combined effects of symptoms of ADHD and insomnia, in addition to their independent effects, on QoL, productivity, and health care use, thereby controlling for a wide range of possible comorbidities and confounders. Methods: Data from the third wave of the Netherlands Mental Health Survey and Incidence Study-2 were used, involving N = 4618 from the general population. Both the inattention and the hyperactivity ADHD symptom dimensions were studied, assessed by the ASRS Screener. Results: Mental functioning and productivity were negatively associated with the co-occurrence of ADHD and insomnia symptoms, even after adjusting for comorbidity and confounders. The results show no indication of differences between inattention and hyperactivity. Poorer physical functioning and health care use were not directly influenced by the interaction between ADHD and insomnia. Conclusions: People with both ADHD and sleep problems have increased risk for poorer mental functioning and productivity loss. These results underscore the importance of screening for sleep problems when ADHD symptoms are present, and vice versa, and to target both disorders during treatment.